2023
DOI: 10.1590/s0102-0536-2023-e2478
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality and antioxidant enzymes activity in eggplant seeds with different ages and resting periods after harvest

Abstract: Constant changes during the seed maturation process affect its final quality and the post-harvest fruit resting, which can improve seed physiological quality. Therefore, the objective of this study was to evaluate the physiological and enzymatic activities of eggplant seeds extracted from fruits harvested at different ages and resting periods after harvest. Fruits were harvested presenting different colors at 40, 50, 60, and 70 days after anthesis (DAA) and rested for 0 (freshly harvested fruits), 10, and 20 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Accumulation of structural proteins such as late embryonic abundants (LEAs) has been reported to be high at 60 DAA in sweet pepper [41]. A study in S. melongena revealed that the levels of CAT, SOD and POX antioxidant enzymes were high in seeds harvested at 40 DAA with a progressive decrease up to 60DAA (maturation stage) and an increase after this period [65]. A similar observation in the activity of CAT and SOD was made in sweet pepper, with a decrease in their activity until maturation and an increase thereafter [66].…”
Section: Changes In Biochemical Seed Quality During Seed Development ...mentioning
confidence: 99%
“…Accumulation of structural proteins such as late embryonic abundants (LEAs) has been reported to be high at 60 DAA in sweet pepper [41]. A study in S. melongena revealed that the levels of CAT, SOD and POX antioxidant enzymes were high in seeds harvested at 40 DAA with a progressive decrease up to 60DAA (maturation stage) and an increase after this period [65]. A similar observation in the activity of CAT and SOD was made in sweet pepper, with a decrease in their activity until maturation and an increase thereafter [66].…”
Section: Changes In Biochemical Seed Quality During Seed Development ...mentioning
confidence: 99%